Combining walking and relaxation for stress reduction—A randomized cross‐over trial in healthy adults. (25th August 2017) - Matzer, Franziska; Nagele, Eva; Lerch, Nikolaus; Vajda, Christian; Fazekas, Christian
Abstract: Both physical activity and relaxation have stress‐relieving potential. This study investigates their combined impact on the relaxation response while considering participants' initial stress level. In a randomized cross‐over trial, 81 healthy adults completed 4 types of short‐term interventions for stress reduction, each lasting for 1 hr: (1) physical activity (walking) combined with resting, (2) walking combined with balneotherapy, (3) combined resting and balneotherapy, and (4) resting only. Saliva cortisol, blood pressure, state of mood, and relaxation were measured preintervention and postintervention. Stress levels were determined by validated questionnaires. All interventions were associated with relaxation responses in the variables saliva cortisol, blood pressure, state of mood, and subjective relaxation. No significant differences were found regarding the reduction of salivary cortisol ( F = 1.30; p = .281). The systolic blood pressure was reduced best when walking was combined with balneotherapy or resting ( F = 7.34; p < .001). Participants with high stress levels ( n = 25) felt more alert after interventions including balneotherapy, whereas they reported an increase of tiredness when walking was combined with resting ( F = 3.20; p = .044). Results suggest that combining physical activity and relaxation (resting or balneotherapy) is an advantageous short‐term strategy for stress reduction as systolic blood pressure is reduced best while similar levels of relaxation can be obtained.